Kajian Empiris terhadap Struktur Modal Perusahaan di Industri Manufaktur - Astutik, Dwi; Ristanto, Hesti; Krisnawati, Hani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2020)
The purpose of this study is to conduct an empirical test of the effect between profitability and liquidity on capital structure. The object of research is conducted on companies that have gone public and are included in the Manufacturing industry. Retrieval of data using a combination of methods by firm and by years, and obtained 589 data. The test results prove that partially, profitability and liquidity have a negative and significant effect on capital structure. Suggestions that can be recommended for academics can be used as a reference as the development of testing of pecking order theory. For the parties in the managerial level of the company, they become the guidelines in making decisions in preparing their capital structure. For potential investors and investors, the results of this study can be used as a material consideration from the fundamental aspects of investment decision making.